Os impactos da globalização e da reestruturação produtiva no mundo do trabalho: a exigência da Língua Inglesa como competência técnica no mercado de trabalho no Maranhão - Aranha, Marize Barros Rocha (2006)
Research on the demand of the English Language as a technical competence in the marketplace in the State of Maranhão, presenting as its background, the globalization process and the productive re-structuration in the labor world. An investigation was carried out at a local enterprise, ALUMAR, which deals with high technological innovation, in order to detect if the company is requiring the appropriate English knowledge from its employees, and to which positions this linguistic competence is indispensable to develop their performance. In order to reach this goal, some job agencies were investigated to identify to what extent the workers are fulfilling the necessary requirements of the laboring market in the professional qualification field. The methodology applied was a study of case with focus on a very expressive job agency in Maranhão. At the end of this research, it can be realized that there is a consider demand of the English Language by the company. In the meantime the most of the workers do not have this competence, and among those who have this competence, it is seen only as a step to the marketplace, not to be, mainly, a cultured citizen.